2008
DOI: 10.1055/s-0028-1085424
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Clinical Use of a Novel Aiming Device for Frameless Stereotactic Brain Biopsy

Abstract: Aiming devices enable the use of neuronavigation systems for rigid instrument guidance mimicking the possibilities of a frame-based system without having a stereotactic frame affixed to the skull. The aim of the presented work was to investigate the phantom targeting accuracy of the Vertek aiming device (Medtronic Inc., Louisville, USA) and whether it can be safely and accurately applied in a concept of minimally invasive brain biopsy in which multi-modal image fusion, image-to-patient registration and head im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 32 publications
(51 reference statements)
0
42
0
Order By: Relevance
“…The authors also added that specific attention and adjustments needed to be made with the operative setup to avoid line-of-sight issues with the optical tracking technology. In addition, Widmann et al [7] reported a mean error of 1.5 ± 0.8 mm for the Medtronic StealthStation optically-based navigation system with the Vertek instrument positioner when targeting 100 points in a plastic head phantom using CT imaging. In a review of EM-based tracking technology, Rosenow and Sootsman [14] reported similar accuracy under ideal conditions for optically tracking technologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also added that specific attention and adjustments needed to be made with the operative setup to avoid line-of-sight issues with the optical tracking technology. In addition, Widmann et al [7] reported a mean error of 1.5 ± 0.8 mm for the Medtronic StealthStation optically-based navigation system with the Vertek instrument positioner when targeting 100 points in a plastic head phantom using CT imaging. In a review of EM-based tracking technology, Rosenow and Sootsman [14] reported similar accuracy under ideal conditions for optically tracking technologies.…”
Section: Discussionmentioning
confidence: 99%
“…However, for needle placements for biopsies of small, deep-seated targets and electrode placement for deep-brain stimulation, frame-based stereotaxy is still considered by many as the gold standard due to its mechanical precision [3,4]. The advent of cranial stabilization system and skull-mounted trajectory guides in the early 2000s expanded traditional stereotactic indications for neuronavigation as they provided a fairly rigid platform [5,6,7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Registration templates are denture fixed acrylic templates with integrated fiducial markers (5,30). External registration frames are head-surrounding constructions with markers, which are connected to a resin template or a vacuum mouthpiece (15)(16)(17)(31)(32)(33). Markers usually have to be manually defined in the image data.…”
Section: Registration Techniquementioning
confidence: 99%
“…As a helpful tool in 3D navigation, aiming devices that are linked to the image-guided surgery navigation system allow for an accurate alignment of the trajectory and guidance of the PTC needle to the target [10][11][12][13]. The electromagnetic tracking system measures the real-time position of surgical tools and fiducials attached to the patient's anatomy.…”
Section: System Calibration and Registrationmentioning
confidence: 99%